2020
DOI: 10.11645/14.1.2695
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy engagement

Abstract: The current research sought to identify what skills, knowledge, and behaviours (SKBs) in advocacy engagement are closely associated with information literacy skills. The paper examines what role information literacy (IL) skills play in making one an effective advocate by drawing on everyday life situations that involve advocacy such as self-advocacy, social advocacy, patient advocacy, parent advocacy, and policy advocacy. A rapid scoping review was completed using articles published within the last ten years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
1
0
2
Order By: Relevance
“…2,3 Alongside these organizations, many researchers have found that developing this skillset correlates to improved self-efficacy and can foster effective learning. [5][6][7] These researchers and institutions come to similar conclusions: an information literate society is necessary to create an understanding and collaborative society.…”
Section: Importance Of Information Literacymentioning
confidence: 93%
“…2,3 Alongside these organizations, many researchers have found that developing this skillset correlates to improved self-efficacy and can foster effective learning. [5][6][7] These researchers and institutions come to similar conclusions: an information literate society is necessary to create an understanding and collaborative society.…”
Section: Importance Of Information Literacymentioning
confidence: 93%
“…Meanwhile, scientists’ political self-disclosure might make them appear more competent. For someone’s advocacy to be effective, they should be equipped with knowledge and skill (Nzomo and Fehrmann, 2020). Therefore, a scientist’s political self-disclosure may signal the scientist’s competency as an advocate to lay publics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Toto omezení tedy zajišťuje aktuálnost zdrojů. Některé studie pracují s delšími časovými obdobími (Nzomo & Fehrmann, 2020;Pashkova-Balkenhol et al, 2019), ale takový postup by pro nás byl irelevantní. Výsledky jsme omezily na ty, ke kterým bylo možné bezplatně přistupovat, tedy byly publikovány pod nějakou formou Open Access licence.…”
Section: Metodologieunclassified
“…Rozvinutá informační gramotnost představuje cestu jak k úspěšnému fungování v běžné životě (Aillerie & McNicol, 2018;Yosida, 2018), tak v oblasti pracovní (Nzomo & Fehrmann, 2020). Odráží se ale také na schopnosti reflektovat a vyhodnocovat informace týkající se zdraví (Camiling, 2019;Mendez et al, 2019).…”
Section: Analýzaunclassified